Magnesium depletion, metabolic impairment, and cardiac alterations: the NAKO-MRI study with Mendelian randomization - Shugaa Addin, Nuha; Schuppert, Christopher; Full, Peter M.; Brenner, Hermann; Dörr, Marcus; Keil, Thomas; von Krüchten, Ricarda; Meinel, Felix G; Niendorf, Thoralf; Pischon, Tobias; Schmidt, Börge; Schulz-Menger, Jeanette; et al. (The journal of clinical endocrinology & metabolism, 2025)
Magnesium deficiency may contribute to subclinical cardiac changes, particularly metabolic diastolic cardiomyopathy.To investigate the association between magnesium depletion, metabolic syndrome (MetS), and magnetic resonance imaging (MRI)-derived cardiac alterations in a population-based sample.We cross-sectionally analyzed participants (N = 9568) from the baseline examination of the German National Cohort who underwent whole-body MRI. Associations of serum magnesium and magnesium depletion score (MDS) with MetS and cardiac alterations were assessed using multivariable logistic and linear regression, respectively. Two-sample Mendelian Randomization was performed to evaluate the potential causal relationship between serum magnesium and MRI-derived cardiac parameters.Our analysis revealed no correlation between serum magnesium and MDS (Spearman's rho = 0.065; P < .001). A 1-SD increase in serum magnesium was associated with lower MetS prevalence (odds ratio, 0.93 [95% CI, 0.88-0.99]) and reduced left and right ventricular systolic and diastolic volumes. Higher MDS, indicating magnesium deficiency, was linked to increased MetS prevalence (OR per 1 unit, 1.32 [95% CI, 1.23-1.41]) and its individual components. Furthermore, higher MDS was associated with increased left ventricular remodeling index (estimate, 0.012 g/mL [95% CI, 0.008-0.017]) and decreased left ventricular end-diastolic volume (estimate, −1.132 mL/m2 [95% CI, −1.538 to −0.727]), indicating concentric hypertrophy. Two-sample Mendelian Randomization suggested no causal relationship between serum magnesium and MRI-derived cardiac markers.Magnesium depletion may serve as an early indicator of cardiac impairment. However, Mendelian Randomization results do not support a causal role of serum magnesium on cardiac structure and morphology.
Gesehen am 19.02.2026